Risk, safety, and clinical practice health care through the lens of risk - Heyman, Bob. (Oxford : Oxford University Press, 2010)
This introductory text focuses on the underlying generic issues of risk management in health care. It allows the reader to analyse risk management issues and to critically evaluate the claims made about existing and new technologies, in an informed way.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Medical care -- Safety measures; Health facilities -- Risk management; Hospitals -- Risk management